Thermal convection in the crust of the dwarf planet – I. Ceres. Issue 4 (27th April 2020) - Formisano, M; Federico, C; Castillo-Rogez, J; De Sanctis, M C; Magni, G
ABSTRACT: Ceres is the largest body in the Main Belt, and it is characterized by a large abundance of water ice in its interior. This feature is suggested by its relatively low bulk density (2162 kg m −3 ), while its partial differentiation into a rocky core and icy crust is suggested by several geological and geochemical features: minerals and salts produced by aqueous alteration, icy patches on the surface, and lobate morphology interpreted as surface flows. In this work, we explore how the composition can influence the characteristics of thermal convection in the crust of Ceres. Our results suggest that the onset of thermal convection is difficult and when it occurs, it is short lived, which could imply that Ceres preserved deep liquid until present, as recently suggested by the work of Castillo-Rogez et al. Moreover, cryovolcanism could be driven by diapirism (chemical convection) rather than thermal convection.